Surviving the terror of the deep: a vibrio vulnificus case report - Zainuddin, Nurnabilah; Mat Nasir, Nurathirah; Samsuddin, Rinni Damayanti; Tengku Jamaluddin, Tengku Zetty Maztura; Ibrahim, Rosni (Universiti Putra Malaysia, 2023)
Vibrio vulnificus is one of the most virulent pathogenic Vibrio species commonly implicated in gastroenteritis, soft tissue infection and septicemia related to seafood consumption or seawater contact. We describe a patient who survives a combination of all three common manifestations of V. vulnificus infection. A 40-year-old male patient, who is a known Chronic Hepatitis B with liver cirrhosis and oesophageal varices, presented with intermittent fever, lower limb pain and redness and diarrhea for the past three weeks. He had a history of consuming raw oysters seven days prior to admission. Blood culture showed grew oxidase-positive non-sucrose fermenting Gram-negative bacillus, subsequently identified as Vibrio vulnificus. The patient was treated with intravenous ceftazidime and oral doxycycline for seven days duration. He was discharged well on day ten of admission. This fortunately mild presentation was probably due to a low infective dose of V. vulnificus exposure.